2015
DOI: 10.12989/gae.2015.9.5.569
|View full text |Cite
|
Sign up to set email alerts
|

Nonexistence and non-decoupling of the dissipative potential for geo-materials

Abstract: Currently, the dissipation potential function is dealt with along two principal approaches. One approach is that unique dissipation potential function is used for plasticity and damage which is deemed that these two dissipation processes occur simultaneously and correlate with each other. Another approach is that the energy dissipated due to plasticity and damage are independent of each other. In this paper, sufficient and necessary conditions are given for the existence of dissipation potential in total relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Given the diverse types of underground tunnels, potential hazards caused by groundwater may be treated prior to construction. Accordingly, Liu et al [5] analyzed the damage and degradation process of granite during drying with the water content as the research parameter and the methods of image processing, strength testing, and ultrasonic detection and obtained the patterns of internal fracture propagation and failure. Their study indicated that the drying test changes the initial stress environment of granite and that the decrease in water content is the main reason for the decrease in the cohesion of the internal residual soil, eventually leading to the disintegration and failure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Given the diverse types of underground tunnels, potential hazards caused by groundwater may be treated prior to construction. Accordingly, Liu et al [5] analyzed the damage and degradation process of granite during drying with the water content as the research parameter and the methods of image processing, strength testing, and ultrasonic detection and obtained the patterns of internal fracture propagation and failure. Their study indicated that the drying test changes the initial stress environment of granite and that the decrease in water content is the main reason for the decrease in the cohesion of the internal residual soil, eventually leading to the disintegration and failure of the material.…”
Section: Introductionmentioning
confidence: 99%